The legacy of the F344 rat as a cancer bioassay model (a retrospective summary of three common F344 rat neoplasms) - Robert R. Maronpot; Abraham Nyska; Jennifer E. Foreman; Yuval Ramot (2016)
The Fischer 344 (F344) rat was used by the National Toxicology Program (NTP) for over 5 decades for toxicity and carcinogenicity studies. However, in 2006, the NTP decided to switch to a different rat stock due largely to high background control incidences of Leydig cell tumors (LCTs) and mononuclear cell leukemia (MNCL), also known as large granular lymphocytic (LGL) leukemia. In the current review, we aim (1) to provide a summary of NTP bioassays with treatment-associated effects involving MNCL and LCTs in addition to male F344-specific tunica vaginalis mesothelioma (TVM); (2) to describe important pathobiological differences between these F344 rat tumor responses and similar target tissue-tumor response in humans; and (3) to present the NTP reasons for switching away from the F344 rat. We show that due to the highly variable background incidence of F344 MNCL, more reliance on historical control data than is usual for most tumor responses is warranted to evaluate potential effect of any chemical treatment in this rat strain. The high spontaneous incidence of LCTs in the testes of male F344 rats has made this tumor endpoint of little practical use in identifying potential testicular carcinogenic responses. TVM responses in F344 rats have a biological plausible relationship to LCTs unlike TVM in humans. Given their high spontaneous background incidence and species-specific biology, we contend that MNCL and LCT, along with TVM responses, in F344 rat carcinogenicity studies are inappropriate tumor types for human health risk assessment and lack relevance in predicting human carcinogenicity.